Infant Massage As A Stunting Prevention Intervention: A Knowledge Assessment Of Mothers In Gedongan Village - Noorrahmah, Azkia; Susilo , Taufik Eko; Rahman , Farid; Naufal , Adnan Faris; Pristianto, Arif; Fatmarizka , Tiara (Jurnal Pengabdian Mandiri, 2025)
Stunting is a long-term nutritional disorder that ultimately affects a child's physical and cognitive development. One non-pharmacological intervention to prevent stunting is baby massage, which can stimulate appetite, improve blood circulation, and provide sensory and motor stimulation. This study aims to evaluate the effectiveness of education about baby massage in increasing mothers' knowledge of stunting prevention. The method used was a one-group pretest-posttest design involving 14 mothers in Gedongan Village, Sukoharjo. The intervention was conducted through socialization, baby massage practice, and the distribution of leaflets. The analysis results showed a significant increase in mothers' knowledge levels after the intervention, with the category of good knowledge rising from 64.3% to 92.9%, while the poor category decreased from 35.7% to 7.1% (p = 0.025). These findings indicate that education about baby massage effectively enhances mothers' understanding of stunting prevention. Therefore, similar educational programs should be integrated into community-based stunting prevention efforts to support optimal child growth.